FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN IBU BALITA DALAM MELAKUKAN KUNJUNGAN ULANG PADA PROGRAM MTBS (MANAJEMEN TERPADU BALITA SAKIT) DI PUSKESMAS BUNGA RAYA - Siska Indrayani; Surisna Okrianti (Ensiklopedia of Journal, 2022)
MTBS ( Management Integrated toddler sick ) is handling toddler sick at the health center in the form of treatment and counseling for To do visit repeat . Destination conducted study this for know the " factors that influence " obedience mother toddler in To do visit repeat on the IMCI program at the Puskesmas Bungaraya Kab. Siak ". Type study is quantitative , design analytic with approach Cross sectional . Amount sample is part from characteristics possessed _ population that is mother who has toddler . Technique taking sample is  Accidental Sampling is as many as 78 respondents . Data processing is carried out with computerized programs and analyzed by univariate and bivariate . Results study show that there is influence mean Among knowledge , attitude and role officer health to obedience mother toddler in To do visit repeat MTBS, where respectively P value 0.003 and OR = 4.952 , P value 0.016 and OR = 3.765 and P value 0.015 and OR = 3.800. So could drawn conclusion that mother who has toddler with knowledge 4,952 times high , attitude positive 3,765 times, and there is role officer 3,800 times for obey To do visit reset MTBS. Based on results study it is hoped that the officers health give counseling about MTBS so that increase understanding mother who has toddler in To do visit repeat .